A synergetic wellness model for first responders targeting cardiovascular risk through myofascial release, nutrition, and breathwork - Burgess, Kimberly (My University, 2025)
First responders, including firefighters, paramedics, and law enforcement officers, face an escalating health crisis fueled by chronic psychological stress, physical trauma, and occupational strain. Elevated rates of myocardial infarction, substance use, PTSD, and suicide persist despite growing awareness and national intervention efforts. This thesis proposes a trauma-informed, integrative wellness model designed to enhance both cardiovascular and psychological resilience in first responders through three synergistic modalities: myofascial release therapy (MFR), structured breathwork, and targeted nutritional intervention. Drawing on over 60 peer-reviewed studies, this research outlines a theoretically grounded, 12-month randomized controlled trial involving 180 career firefighters across three study arms: control, written-only, and a hands-on intervention group receiving weekly MFR, daily breathwork, and biweekly group nutrition sessions. Primary outcomes include myocardial infarction risk (biomarkers, blood pressure, HRV), psychological stress (PSS, cortisol), substance use (AUDIT-C), and quality of life (SF-36, WHOQOL-BREF), with secondary measures assessing sleep, anxiety, depression, and physical activity. Recent evidence illustrates that nutrition profoundly influences fascial elasticity, inflammation, and recovery potential, making it a critical determinant of MFR efficacy. Additionally, manual therapy modalities such as MFR have demonstrated measurable reductions in anxiety symptoms among first responders and trauma-exposed populations, due in part to their impact on autonomic recalibration and interoception. Furthermore, emerging data from wildfire deployments underscores the need for systemic interventions to address the long-term physical and emotional toll on EMS personnel. This thesis argues that the integration of these three modalities, each with evidence of standalone benefit, can produce compounding, cross-disciplinary effects. By addressing the biological, emotional, and somatic dimensions of stress through a unified protocol, this model moves beyond symptom management toward root-cause prevention and long-term resilience building. The proposed framework represents a scalable, low-cost solution with the potential to reshape occupational health standards in high-risk service professions.
Keywords: First responders; Myofascial release; Breathwork; Nutrition; Cardiovascular; Synergetic